The role of constitutional judiciary in the protection of academic freedom in Iraq: Comparative study - عباس سارة فاضل; يونس مها بهجت (Journal of Legal Sciences, 2021)
Academic freedom is a human right, and if human rights are general rights, academic freedom is a special freedom for members of the academic community. Despite the modernity of the term "academic freedom", its content was not the result of the contemporary state of scientific academic bodies, That the development of the importance of this term coincided with the development of the exercise of public freedoms, and increased interest in and protection, so the number and expanded images of academic freedom, and was a manifestation of interest in this freedom to try to determine the content or what it is and pictures, The first of these guarantees is the supervision of the constitutionality of the laws, which are carried out through judicial supervision and it works to ascertain the extent to which the legislative or executive work conforms to the provisions of the Constitution. The mismatches mean the repeal of the law which did not conform to the provisions of the Constitution. Related to its general meaning, which we examined in the form of two subjects, the first of which we devoted to the definition of academic freedom, and dealt in the second role of the constitutional judiciary in the protection of academic freedom.